2016
DOI: 10.1111/bcp.13032
|View full text |Cite
|
Sign up to set email alerts
|

Performance of trigger tools in identifying adverse drug events in emergency department patients: a validation study

Abstract: Keywords drug-related side effects and adverse reactions, emergency service, health care, hospital, quality indicators, trigger tools AIMSTrigger tools are retrospective surveillance methods that can be used to identify adverse drug events (ADEs), unintended and harmful effects of medications, in medical records. Trigger tools are used in quality improvement, public health surveillance and research activities. The objective of the study was to evaluate the performance of trigger tools in identifying ADEs. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 47 publications
1
35
0
3
Order By: Relevance
“…Moreover, a recent prospective cohort study found that both of these trigger tools had sensitivities of < 0.20 for identifying ED ADEs. 28 Based on these facts, both models reported in this article identify bleeding ADEs well enough to be potentially useful as a trigger tool for quality improvement and safety surveillance activities. The CART model is particularly promising because of its greater transparency and sensitivity, and also because it could be implemented much the same as typical trigger tools.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, a recent prospective cohort study found that both of these trigger tools had sensitivities of < 0.20 for identifying ED ADEs. 28 Based on these facts, both models reported in this article identify bleeding ADEs well enough to be potentially useful as a trigger tool for quality improvement and safety surveillance activities. The CART model is particularly promising because of its greater transparency and sensitivity, and also because it could be implemented much the same as typical trigger tools.…”
Section: Discussionmentioning
confidence: 94%
“…The conscious work of end-users cannot be replaced by analyzing traces of data left as documentation within medical records that were never specifically intended to capture robust ADE information [28,29]. Instead, we stress the need to rethink the rationale and systems designed for reporting ADEs.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study carried out in Canada has investigated these parameters and observed a low sensitivity, from 2.6 to 15.8%, depending on the trigger, but a high specificity. The authors suggest that more sensitive triggers can be developed using clinical decision-making methods, in which clinical judgment is initially used to define options as predictors 28 .…”
Section: And In This Study No Patients Needed Hospitalizationmentioning
confidence: 99%